Beyond physical health: the role of psychosocial challenges and stigma in tackling the COVID-19 pandemic—A scoping review - Jain, Lakshit; Bhivandkar, Siddhi; Baqir, Huma; Shoib, Sheikh; Nimavat, Nirav; Mohan, Anmol; Zubair, Aarij Shakil; Jawad, Muhammad Youshay; Muhammed, Nazar; Ahmed, Rizwan; Sachdeva, Vishi; Ahmed, Saeed (Frontiers in Psychiatry, 2023)
Introduction The socio-cultural response to the Coronavirus Disease 2019 (COVID-19) and the level of adherence to evidence-based guidelines played a crucial role in determining the morbidity and mortality outcomes during the pandemic. This review aims to evaluate the impact of stigma and psycho-socio-cultural challenges on efforts to control the COVID-19 pandemic and to identify ways to mitigate such challenges in future pandemics. Methods: Using keywords including COVID-19, coronavirus, stigma, and psychosocial challenges among others, the authors searched seven major databases with a time limitation of July 2021, which yielded 2038 results. Out of these, 15 papers were included in this review. Results: The findings of the review indicated that several psychosocial, socioeconomic, and ethnocultural factors are linked to the transmission and control of COVID-19. The research revealed that stigma and related psychosocial challenges, such as anxiety, fear, and stigma-driven social isolation, have resulted in serious mental health problems. Discussion: The review underscores the negative impact of stigma on COVID-19 patients, survivors, and the general population. Addressing stigma and psychosocial challenges is crucial to effectively manage the current pandemic and to prevent similar challenges during future public health crises.